2001
DOI: 10.1161/hh1801.097034
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 Reduces VEGF-Stimulated Leukocyte Adhesion to Endothelial Cells by Reducing ICAM-1, VCAM-1, and E-Selectin Expression

Abstract: Vascular endothelial growth factor (VEGF) and angiopoietin-1 (Ang1) are potent vasculogenic and angiogenic factors that hold promise as a means to produce therapeutic vascularization and angiogenesis. However, VEGF also acts as a proinflammatory cytokine by inducing adhesion molecules that bind leukocytes to endothelial cells, an initial and essential step toward inflammation. In the present study, we used human umbilical vascular endothelial cells (HUVECs) to examine the effect of Ang1 on VEGF-induced express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
220
4
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(241 citation statements)
references
References 11 publications
14
220
4
3
Order By: Relevance
“…It is also possible that the plasma exudates may readily pass the inflamed mucosa and reach the airway lumen through leaky epithelium, thus compromising epithelial integrity and reducing ciliary function and mucus clearance (Foster et al, 1982;Persson, 1996). Although some investigators have described a role for Ang1 in promoting chemotaxis and migration of leukocytes in vitro (Feistritzer et al, 2004;Lemieux et al, 2005), Ang1 has also been shown to reduce leukocyte trafficking in inflammation through the modulation of various inflammatory mediators (Kim et al, 2001;Pizurki et al, 2003;Witzenbichler et al, 2005). Th2 cytokines, adhesion molecules, chemokines, and VEGF play a crucial role in the chemotactic responses for leukocytes, including eosinophils (Wegner et al, 1990;Montefort and Holgate, 1991;Moser et al, 1992;Seder et al, 1992;Foster et al, 1996;Pawankar et al, 1997;Dabbagh et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the plasma exudates may readily pass the inflamed mucosa and reach the airway lumen through leaky epithelium, thus compromising epithelial integrity and reducing ciliary function and mucus clearance (Foster et al, 1982;Persson, 1996). Although some investigators have described a role for Ang1 in promoting chemotaxis and migration of leukocytes in vitro (Feistritzer et al, 2004;Lemieux et al, 2005), Ang1 has also been shown to reduce leukocyte trafficking in inflammation through the modulation of various inflammatory mediators (Kim et al, 2001;Pizurki et al, 2003;Witzenbichler et al, 2005). Th2 cytokines, adhesion molecules, chemokines, and VEGF play a crucial role in the chemotactic responses for leukocytes, including eosinophils (Wegner et al, 1990;Montefort and Holgate, 1991;Moser et al, 1992;Seder et al, 1992;Foster et al, 1996;Pawankar et al, 1997;Dabbagh et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Ang1-and Tie2-deficient mice have similar phenotypes characterized by embryonic lethality with severe vascular remodeling defects, insufficient vessel stabilization, and perturbed vascular maturation (Sato et al, 1993;Suri et al, 1996). In addition, Ang1 can counteract VEGF-induced side effects (Thurston et al, 2000;Kim et al, 2001) while having an additive effect on vessel formation (Chae et al, 2000;Thurston et al, 2000). These observations have suggested that Ang1 has potential therapeutic applications in inducing angiogenesis, enhancing endothelial cell survival, and preventing vascular leakage.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF-A stimulation of human umbilical vein endothelial cells increases the expression of adhesion molecules, such as ICAM-1, VCAM-1, and selectins (68,75). This induction of adhesion molecule expression increases in vitro leukocyte adhesion under static conditions, which occurs through the activation of VEGF-R2 (75,76). Importantly, we have recently reported that VEGF-A stimulates increased ICAM-1 expression on distal colon microvascular endothelium, which facilitates neutrophil and T cell adhesion in a CD18-dependent manner (55).…”
Section: Angiogenic Mediators In Ibd and Experimental Colitismentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 16 angiopoietin-1 (Ang1) has both angiogenic and anti-inflammatory properties [55,56,57]. For example, binding of Ang1 to Tie2 inhibits the NF-B-dependent expression of adhesion molecules, decreases the permeability of endothelial monolayers and impedes TNF-induced transmigration of leukocytes [58,59]. ABIN-2 was found to interact with the cytoplasmic tail of Tie2 via a domain encompassing AHD1.…”
Section: Abin-2mentioning
confidence: 99%